Community Mobilization Led by Lay Actor, a Directed Participation in Tax Culture - Utomo, Rachmad (Jurnal Ilmiah Administrasi Publik, 2021)
Community leaders indeed become strategic actors for the government. In Pondok Aren, a meatball seller has led the UMKM Sahabat Pajak (USP) or micro, small, and medium enterprises (SME) community tax-friendly, they were successfully directed to mobilize a social movement "We're great at paying taxes" (Bayar Pajak Untung). This study aims to describe how Kantor Pelayanan Pajak (tax office) Pondok Aren seeks lay actors and builds their capacity to become community movers. With the ethnographic research method, the findings show that the government needs to be diligent in looking for them, getting to explore them from the original place every day they are working because persuading citizens with social capital is not enough. The government should not be fascinated by educational and professional backgrounds because it does not guarantee the noble attitude of citizens who voluntarily participate in building a functioning society towards social welfare.